Poverty, inequality, and inclusive growth in Asia measurement, policy issues, and country studies - Zhuang, Juzhong (Anthem Press ; Asian Development Bank, 2010)
"Examines why Asia needs inclusive growth, what policy ingredients an inclusive growth strategy entails, and how such a strategy can lead to benefits of growth being more equitably shared."--Publisher's description.